Protective effect of limonin against doxorubicin-induced cardiotoxicity via activating nuclear factor - like 2 and Sirtuin 2 signaling pathways. Issue 1 (1st January 2021) - Deng, Jie; Huang, Min; Wu, Hao
ABSTRACT: The anti-tumor and anti-inflammatory effects of limonin have been established, here, we aim to explore whether limonin can induce protective effects against doxorubicin (DOX)-mediated cardiotoxicity which limits its clinical application. We found that limonin attenuated DOX-mediated cytoxicology of myocardial cell line H9C2 by measuring cell viability and reactive oxygen species (ROS) level. Additionally, limonin ameliorates DOX-induced cardiac injury in rat by examining the activity of lactate dehydrogenase (LDH), superoxide dismutase (SOD), glutathione (GSH), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) concentration, and histopathological changes. Mechanistically, it was shown that limonin partially abrogated the inhibition of Nuclear factor – like 2 and Sirtuin 2 signaling induced by DOX. Furthermore, limonin-mediated protective effects on DOX-mediated cytoxicology of H9C2 were rescued by a Sirt2-specific inhibitor or siRNA against Sirt2. Thus, this work reveals that limonin can suppress DOX-mediated cardiotoxicity by activating Nrf2 and Sirt2 signaling. Graphical abstract: